Characterisation of mixture preparation in lean premixed prevaporised combustor modules by planar laser fluorescence imaging and computational fluid dynamics modelling - Davoudi, Henrik (Cranfield University, 2001)
In order to minimise the environmental impact of combustion emissions, radically new combustor concepts are under development. Lean premixed prevaporised (LPP) combustion has the greatest potential to achieve low emissions, particularly with respect to oxides of nitrogen. The role of fuel preparation is crucial in the success of the LPP combustor concept. Planar laser-induced fluorescence (PLIF) has been used to determine fuel placement and concentration, while computational fluid dynamics (CFD) has provided insight into the internal aerodynamics of two premixers. In order to determine the local equivalence ratios in a realistic device a calibration method, for the PLIF signal, has been derived. The vapour phase fluorescence of naphthalene, in the presence of oxygen, was calibrated against known conditions of temperatures and air-fuel ratios. This calibration was undertaken for an atmospheric and isothermal (non-combusting) flow. With regard to the small engine LPP module, PLIF measurements of the vapour fuel provided images of quantitative local equivalence ratios, at the exit of the premixer. In addition, based on the results of the liquid-phase measurements the evaporated fuel fraction was estimated. The computed droplet trajectories, within the premixing duct, highlighted the importance of the initial fuel dispersion from the injector. Two approaches were identified for improving the vaporisation and increasing the homogeneity of the air-fuel mixture. The large engine LPP module was investigated for several geometries and operating conditions. The evolution of the fuel dispersion, for those geometries, was characterised by PLIF images of the vapour fuel. In addition, the flame position inside the optical premixing duct was captured by video imaging for each geometry. 2D and 3D CFD simulations were performed to provide an insight into the aerodynamics of the premixer. These results were the basis of a schematic fuel jet breakup study, for two different injector configurations. Finally, the operational characteristics of this novel LPP module, featuring a conical centre-body, are discussed.